PATH Influenza Vaccine Project: accelerating the development of new influenza vaccines for low-resource countries. (August 2012) - Neuzil, Kathleen M; Tsvetnitsky, Vadim; Nyari, Linda J; Bright, Rick A; Boslego, John W; ,
The 2009 influenza A/H1N1 pandemic demonstrated that a pandemic influenza virus has the potential to spread more rapidly in today's highly interconnected world than in the past. While pandemic morbidity and mortality are likely to be greatest in low-resource countries, manufacturing capacity and access to influenza vaccines predominantly exist in countries with greater resources and infrastructure. Even with recently expanded manufacturing capacity, the number of doses available within a 6-month timeframe would be inadequate to fully immunize the global population if the decision to implement a global vaccination program were made today. Improved, affordable vaccines are needed to limit the consequences of a global influenza outbreak and protect low-resource populations. PATH's Influenza Vaccine Project is supporting a range of activities in collaboration with private- and public-sector partners to advance the development of promising influenza vaccines that can be accessible and affordable for people in low-resource countries.